A new approach for surgical treatment of chronic Monteggia fracture in children. Issue 6 (June 2019) - Liao, Shijie; Pan, Jie; Lin, Huahao; Xu, Yaofeng; Lu, Rongbin; Wu, Jianping; Zhao, Manjun; Chen, Huilin; Cai, Ming; Ding, Xiaofei; Zhao, Jinmin
Highlights: We provided a new approach for the surgery of chronic Monteggia fractures namely combining anterior and posterior approach. The new combined approach for surgery got a satisfactory outcome. The benefits of the new approach were better exposure, more convenient intraoperative management, and facilitate for radial nerve exploration. Without reconstruction of the annular ligament, redislocation and/or subluxation less occurred in the follow up. Abstract: Purpose: The aim of the study was to investigate the clinical outcomes of a combined anterior and posterior approach for the surgical treatment of chronic Monteggia fractures in children. Materials and methods: From November 2010 to January 2018, 33 patients (27 boys and 6 girls) with chronic Monteggia fracture who were treated surgically by one surgeon of our department were retrospectively analyzed. In the surgical procedure, open reduction and excision of fibrous scar were performed with the anterior Henry's approach, while ulnar osteotomy was carried out with a posterior approach. In cases of unstable radial head reduction, a trans-capitellar K wire was applied. Repair or reconstruction of the annular ligament (ALR) was not undertaken. Results: The average follow-up of the patients was 33.8 months (range 8–87 months). At the last follow-up, Mayor Score and function of flexion and extension showed significant improvement compared to preoperative condition ( p < 0.05). Two patients with palsy of the deep branch of the radial nerve with neurolysis recovered to normal over a 3-month follow-up. Redislocation occurred in two patients while subluxation occurred in one. One patient suffered a mild ischemic contracture but gradually recovered. Other severe complications, nerve injuries, heterotopic ossification, or synostosis, were not noted in the follow-up. Conclusion: A combined anterior and posterior approach for surgery resulted in a satisfactory outcome due to the advantages of better exposure, more convenient intraoperative management, and facilitate for radial nerve exploration. Our study provided a new approach for the surgery of chronic Monteggia fractures.